Validity of synthetic bone as a substitute for osteoporotic cadaveric femoral heads in mechanical testing: A biomechanical study. Issue 4 (April 2012) - O'Neill, F.; Condon, F.; McGloughlin, T.; Lenehan, B.; Coffey, C.; Walsh, M.
Abstract : Introduction: The objective of this study was to determine if a synthetic bone substitute would provide results similar to bone from osteoporotic femoral heads during in vitro testing with orthopaedic implants. If the synthetic material could produce results similar to those of the osteoporotic bone, it could reduce or eliminate the need for testing of implants on bone. Methods: Pushout studies were performed with the dynamic hip screw (DHS) and the DHS Blade in both cadaveric femoral heads and artificial bone substitutes in the form of polyurethane foam blocks of different density. The pushout studies were performed as a means of comparing the force displacement curves produced by each implant within each material. Results: The results demonstrated that test material with a density of 0.16 g/cm 3 (block A) produced qualitatively similar force displacement curves for the DHS and qualitatively and quantitatively similar force displacement curves for the DHS Blade, whereas the test material with a density of 0.08 g/cm 3 (block B) did not produce results that were predictive of those recorded within the osteoporotic cadaveric femoral heads. Conclusion: This study demonstrates that synthetic material with a density of 0.16 g/cm 3 can provide a good substitute for cadaveric osteoporotic femoral heads in the testing of implants. However we do recognise that no synthetic material can be considered as a definitive substitute for bone, therefore studies performed with artificial bone substrates may need to be validated by further testing with a small bone sample in order to produce conclusive results.